(untitled) (European Journal of Pure and Applied Mathematics, 2024)
A graph or molecular graph’s overall resilience and connectedness are gauged by the Sombor Index (SOI). It is an improved version of the conventional SOI that is designed to capture ambiguity in the relationships between nodes or atoms. This indicator aids in assessing the network’s resilience and stability in erratic circumstances. We have investigated the charac- teristics of the SOI of neutrosophic graphs (N Gs) in this study. The association between the neutrosophic first Zagreb Index (N FZI) of N Gs and the neutrosophic Sombor Index (N SI) was revealed in the study. The application of SOI based on Site Selection for Thermal Power Plants in N Gs is finally covered.